2014
DOI: 10.1002/ejic.201301278
|View full text |Cite
|
Sign up to set email alerts
|

A Propeller‐Shaped, Triazine‐Linked Porphyrin Triad as Efficient Sensitizer for Dye‐Sensitized Solar Cells

Abstract: A propeller-shaped, triazine-linked, unsymmetrical porphyrin triad -consisting of two zinc-metallated porphyrin units and one free-base porphyrin unit that is functionalized by a carboxylic acid -has been synthesized by stepwise amination reactions of cyanuric chloride. Photophysical, electrochemical, and DFT studies of the triad revealed no significant electronic interactions between the porphyrin units in the triad ground state but frontier orbital energy levels suitable for use as sensitizer in dye-sensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 112 publications
(23 reference statements)
0
26
0
1
Order By: Relevance
“…To gain insights into the electronic structures for the frontier orbitals of the porphyrins, density functional theory calculations were carried out for studied porphyrins at the B3LYP/6-31G(d) level using Gaussian 09 Software [42,43]. Figure 4 illustrates the electron density distributions of studied porphyrins in their respective HOMO, LUMO, LUMO + 1, and LUMO + 2 molecular orbitals.…”
Section: Quantum Chemical Resultsmentioning
confidence: 99%
“…To gain insights into the electronic structures for the frontier orbitals of the porphyrins, density functional theory calculations were carried out for studied porphyrins at the B3LYP/6-31G(d) level using Gaussian 09 Software [42,43]. Figure 4 illustrates the electron density distributions of studied porphyrins in their respective HOMO, LUMO, LUMO + 1, and LUMO + 2 molecular orbitals.…”
Section: Quantum Chemical Resultsmentioning
confidence: 99%
“…The higher PCE value of the 171-based DSSC is attributed to its larger dye loading and higher J sc , V oc , and FF values. Coutsolelos and coworkers 168 synthesized via stepwise amination reactions of cyanuric chloride a propeller shaped, triazine bridged, and unsymmetrical porphyrin triad 172. Photophysical and electrochemical studies of the triad revealed no significant electronic interactions between the porphyrin units in the triad ground state, but the frontier orbital energy levels are suitable for use as sensitizer in DSSCs, as they favor the electron injection and dye regeneration processes.…”
Section: A Dimeric-porphyrinsmentioning
confidence: 99%
“…The synthesis of dyads HOOC-DMP-Ru(bpy)3 and HOOC-(Zn)DMP-Ru(bpy)3 is presented in Scheme 1. The porphyrin derivative 1 [41] was linked to carboxylic acid bipyridine compound (2) [42] via a two-step amide coupling reaction. More specifically, the carboxylic acid substituted bipyridine (2) was initially refluxed in SOCl2 in order to obtain the corresponding acyl chloride, which then reacted with amino porphyrin (1) The four final compounds (HOOC-DMP-tpy-Ru, HOOC-(Zn)DMP-tpy-Ru, HOOC-DMP-Ph and HOOC-(Zn)DMP-Ph) were prepared through the hydrolysis of the methyl ester groups to the desired carboxylic acid anchoring groups.…”
Section: Synthesismentioning
confidence: 99%